Bilateral injury of deep peroneal nerve in the patient after heart transplant - Adam Śmiechowski; Małgorzata Sobieszczańska-Małek (Российский кардиологический журнал, 2020)
In March 2015, a 62-year-old patient with advanced heart failure underwent a failed radiofrequency ablation, followed by paresis of muscles in the anterior compartment of the leg. After rehabilitation, partial recovery of the paresis was achieved. Orthotopic heart transplantation was performed 9 months after ablation at the at the Institute of Cardiology, followed by a bilateral paresis of muscles in the anterior leg compartment. Rehabilitation was implemented. The possible cause of paresis is most likely to be due to food shortages, mainly related to a folic acid deficiency.